Early‐pregnancy BMI, maternal gestational weight gain, and asthma and allergic diseases in children - Ojwang, Vincent; Nwaru, Bright I.; Hanna-Mari, Takkinen; Heli, Tapanainen; Kaila, Minna; Ahonen, Suvi; Niemela, Onni; Haapala, Anna-Maija; Ilonen, Jorma; Toppari, Jorma; Hyoty, Heikki; Veijola, Riitta; et al. (Wiley, 2025)
Background: Association of early pregnancy body mass index (BMI) and maternal gestational weight gain (GWG), and asthma and allergic disease in children is unclear.
Methods: We analyzed data from 3176 mother-child pairs in a prospective birth cohort study. Maternal anthropometric measurements in the first and last antenatal clinic visits were obtained through post-delivery questionnaires to calculate early pregnancy BMI and maternal GWG. Asthma and allergic diseases in children by the age of 5 years was assessed using a validated questionnaire. Furthermore, serum samples were analyzed for IgE antibodies to eight allergens. We applied Cox proportional hazards and logistic regression analyses to estimate the association of early pregnancy BMI and maternal GWG (as continuous variables and categorized into quarters), and asthma, atopic eczema, atopic sensitization, and allergic rhinitis in children.
Results: Neither early pregnancy BMI nor maternal GWG was associated with asthma and allergic disease in children when analyzed as continuous variables. However, compared to the first quarter of GWG (a rate <0.32 kg/week), mothers in the third quarter (rate 0.42-0.52 kg/week) had children with significantly higher odds of developing atopic eczema (adjusted OR 1.49, 95% CI [1.13-1.96]) by 5 years of age.
Conclusion: Association of early pregnancy BMI and maternal GWG, and asthma and allergic disease in children, is inconsistent. High maternal GWG may be associated with increased odds of atopic eczema.